2014
DOI: 10.1021/mp4007612
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lipiodol and Cyclosporin A on the Hepatobiliary Disposition of Doxorubicin in Pigs

Abstract: Doxorubicin (DOX) emulsified in Lipiodol (LIP) is used as local palliative treatment for unresectable intermediate stage hepatocellular carcinoma. The objective of this study was to examine the poorly understood effects of the main excipient in the drug delivery system, LIP, alone or together with cyclosporin A (CsA), on the in vivo liver disposition of DOX and its active metabolite doxorubicinol (DOXol). The advanced, multi-sampling-site, acute pig model was used; samples were collected from three blood vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 60 publications
3
43
0
Order By: Relevance
“…This preclinical study was designed to investigate how lipiodol, administered separately from DOX, affects the tissue concentration and distribution ( K p ) of DOX and DOXol. The first part of the study, regarding multiple site plasma PK and biliary and urinary excretion, has been published previously . The materials and methods used in the in vivo experiment in this second part of the study have been described in detail in the previous article .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This preclinical study was designed to investigate how lipiodol, administered separately from DOX, affects the tissue concentration and distribution ( K p ) of DOX and DOXol. The first part of the study, regarding multiple site plasma PK and biliary and urinary excretion, has been published previously . The materials and methods used in the in vivo experiment in this second part of the study have been described in detail in the previous article .…”
Section: Methodsmentioning
confidence: 99%
“…In healthy pig liver, the intracellular concentrations of DOX tended to be higher (78%) after administration of a DOX‐in‐lipiodol emulsion than after administration of DOX‐loaded microparticles . In a subsequent pharmacokinetic (PK) pig study, it was concluded that lipiodol alters neither the plasma concentrations nor the biliary and urinary excretion of DOX and DOXol . That pig study also concluded that ciclosporin (CsA) alters the disposition of DOX and DOXol, probably by inhibition of canalicular biliary secretion .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This point is of major interest as very recently demonstrated in a pig model, which showed that the in vivo distribution of the drug was affected more by the formulation-related properties of the anticancer drug-lipiodol emulsion than by any direct interactions between lipiodol and membrane barriers and/or transport proteins [30].…”
Section: Discussionmentioning
confidence: 97%